Nonfatal Bites by a Sicklefin Lemon Shark Negaprion acutidens on a Surfer in Makemo Atoll (French Polynesia). Issue 3 (31st October 2019) - Clua, Eric E. G.; Haguenauer, Anne
Abstract: Identifying the species and size of sharks responsible for biting humans is essential for developing strategies to prevent these incidents. Here, we use bite wound characteristics and genetic analysis of a tooth fragment extracted from the wounds to identify a sicklefin lemon shark Negaprion acutidens as the perpetrator of nonfatal bites on the legs of an adult male surfer at Makemo atoll (French Polynesia) in January 2018. The bite was superficial, and N. acutidens are fish predators not known to feed on large prey; hence, foraging is an unlikely explanation for this incident rather linked to territoriality. Lemon sharks are occasionally aggressive toward humans and are site attached with relatively small home ranges; hence, avoiding surfing in the area of a previous bite incident is recommended to decrease the risk of future injuries.